Comprehensive Anatomical Investigation of Root of Plumbago Roseus Linn: Anatomical Investigation of Root of Plumbago roseus Linn - Ragunathan Muthuswamy; Senthamarai R (Iranian Journal of Pharmaceutical Sciences, 2013)
Root of Plumbago indica Linn is used in ayurveda and siddha medicine for the treatment of colic inflammations bronchitis, helminthiasis, hemorrhoids, elephantiasis, hepatosplenomegaly, amenorrhea, odontalgia, piles, and diabetes. The present study aims to investigate the anatomical characters of thin and thick root and to confirm the physicochemical characters of the root. Anatomical studies and physiochemical evaluation of root were performed based on the customary protocols mentioned in WHO guidelines and Indian ayurvedic pharmacopoeia. Anatomical studies of root tissues were done as photographs with different magnifications by using Nikon lab photo 2 microscopic Unit. The elemental analysis was done by using perkin elmer 5000 atomic absorption spectrophotometer. We compared the anatomy of thin root to thick root; the periderm of the thin root was 70-80 μm thick, whereas in thick root the periderm was measured about 100 μm thick. In powder microscopy, two kinds of fibers were found; Wide fibers were 300-500 μm long and 30 μm wide, Narrow fibers were 340 μm long and 15 μm wide. Vessel elements are estimated about 140 μm long. Physio-chemical parameters such as total and acid-insoluble ash (8.33% w/w, 1.55% w/w, respectively), extractive values (aqueous 11.21% w/w and alcoholic 5.30% w/w) were performed. The study provides the quantitative data that was given assurance to identify and differentiate this species correctly for the purpose of traditional medicinal use.